World - Piloting of Implementation of United Nations Convention Against Corruption (UNCAC) in Honduras - World Bank (Washington, DC, 2022)
This document contains the answers to the self-evaluation questionnaire of Honduras for the Review Mechanism in the implementation of the United Nations Convention against Corruption (UNCAC). To facilitate the review of Party States (Dominican Republic and Republic of Nauru) a brief summary of the criminal proceedings in Honduras, its stakeholders and roles are presented. Also attached are some key definitions that may contribute to understanding the Honduran context in criminal matters, criminal procedure and international cooperation, related to the implementation of UNCAC.